PENGARUH SERTIFIKASI DAN SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU MADRASAH IBTIDAIYAH HAYATUL ISLAM JAKARTA - Budi Utomo, Styo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
Theoretically, this study aims to determine the effect of certification and supervision of school principals on the performance of Madrasah Ibtidaiyah Hayatul Islam teachers. While the practical purpose is to express the symptoms of teacher performance, so that from this study suggestions and recommendations for improvement are proposed. This research uses a qualitative approach with descriptive methods. The population in this study was MI Hayatul Islam’s teachers, amounting to 10 people, and the unit of analysis used as samples were 6 teachers who had passed the certification. The research instrument used was a questionnaire, while the analytical method used was Non Parametric Kruskall Wallis. The results of the study revealed that certification had an effect on the performance of MI Hayatul Islam teachers with KW value of -38,438 <12,5916. Supervision of Headmasters influences the performance of MI Hayatul Islam teachers with KW value of -38.559981 <12.5916. Certification and the supervision of Principal School jointly affect the performance of MI Hayatul Islam’s teachers. The results of the study mentioned that the average effect was not the same as the KW result = 12,534 <12.5916. These could be concluded that the influence of teacher certification and principal supervision toward MI Hayatul Islam teachers who has been certified is different, both in quality and quantity